Menanggulangi Kebencian dan Ekstrimisme Melalui Pendidikan Kewarganegaraan untuk Generasi Toleran - Saputra, Singgih; Subekti, Catur Putra; Jiddan, Muhammad Afif (HUMANIORUM, 2024)
Citizenship Education (PKn) has an important role in helping Indonesian society become more tolerant and face increasing hatred and extremism. In this article, we will discuss how Civics can be used as a means to develop attitudes of tolerance and overcome hatred and extremism through education that is oriented towards nationality and democracy. This research uses a qualitative approach by conducting interviews with several students and this research uses text analysis by analyzing Civics materials such as textbooks, curriculum and teaching materials. In this way, Indonesia's future generations can be helped to become more tolerant and ready to face the challenges that come.